2017
DOI: 10.1051/cagri/2017030
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of an innovation platform to change the management of collective irrigation: a case study from the Office du Niger (Mali)

Abstract: -In the Office du Niger large rice farming irrigation scheme in Mali, water management has been a permanent source of tension between the smallholder tenants and the administration. The transfer of tertiary canal maintenance to the tenant farmers was expected to improve water management but, in practice, that rather led to deterioration. An innovation platform, erected by the CoS-SIS (Convergence of Sciences -Strengthening Innovation Systems) Program, reached a consensual agreement to transfer the maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In this regard, the quality of institutions, particularly the ability to take collective farming in irrigation systems (public resources), is a key factor in determining effective economic performance. However, there is little evidence to show how governance mechanisms (such as exposure and control) and external factors (such as market characteristics and rainfall variability) affect the institutional quality of collective farming in irrigation plans (Soumano & Traoré, 2017). In this section, panel data sets re- results for the overall intercept-for both fixed and random effects of 47.83 percentage points as a baseline (reference), the findings showed that the institutional quality (compliance) may vary (increase or decrease) by a standard deviation of 22.42 across the schemes (Table 4).…”
Section: Mixed Effect Modelmentioning
confidence: 99%
“…In this regard, the quality of institutions, particularly the ability to take collective farming in irrigation systems (public resources), is a key factor in determining effective economic performance. However, there is little evidence to show how governance mechanisms (such as exposure and control) and external factors (such as market characteristics and rainfall variability) affect the institutional quality of collective farming in irrigation plans (Soumano & Traoré, 2017). In this section, panel data sets re- results for the overall intercept-for both fixed and random effects of 47.83 percentage points as a baseline (reference), the findings showed that the institutional quality (compliance) may vary (increase or decrease) by a standard deviation of 22.42 across the schemes (Table 4).…”
Section: Mixed Effect Modelmentioning
confidence: 99%
“…The irrigation system is confronted with perpetual drainage problems during harvest, resulting in high production costs as well as loss of production and/ or quality (VANDERSYPEN, 2007). Farmers do not respect the cleaning obligations of the tertiary canal and related water management tasks (SOUMANO & TRAORE, 2017). The malfunctioning of the irrigation system seems to be the factor contributing to soil degradation in Mali that is very closely link to poor drainage conditions and low water efficiency (BAGAYOKO et al, 2007).…”
Section: Technologymentioning
confidence: 99%
“…This is still high for farmers living in precarious conditions. The rule in force is that any tenant who wouldn't pay the full fees for the use of water; calculated on the basis of the water requirements for rice per hectare allocated; would lose access to the entire area (SOUMANO & TRAORE, 2017). Farmers often prefer to pay for consumer goods such as two-wheeled gear and waste of their hard-won earnings instead of paying their water fees.…”
Section: Government Policymentioning
confidence: 99%
See 1 more Smart Citation